The Protestant Ethic in Hungary. The Puritan Ethic and Its Influence. By Attila K. Molnár. Göttingen: Vandenhoeck & Ruprecht, 2024. 238 pp. 1 map. ISBN 9783525540893. €130.00 hardback - Murdock, Graeme (Church history, 2025)
The Protestant Ethic in Hungary. The Puritan Ethic and Its Influence. By Attila K. Molnár. Göttingen: Vandenhoeck & Ruprecht, 2024. 238 pp. 1 map. ISBN 9783525540893. €130.00 hardback. - Volume 94 Issue 2